ADMINISTRATIVE AND LEGAL PRINCIPLES OF ACTIVITY OF STATE REGISTRARS IN THE FIELD OF STATE REGISTRATION OF RIGHTS - Nikitin, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is a comprehensive analysis of the theoretical and methodological foundations, normative foundations and practical implementation of the legal foundations of the activity of state registrars of Ukraine in the field of state registration of property rights. Research methods: the general philosophical dialectical, systematic, formal-dogmatic and comparative-legal method was used. Results: the legal bases of the activity of state registrars in the field of state registration of property rights to immovable property and their encumbrances were investigated, the peculiarities of the legal status of the state registrar and its role in the registration process were analyzed, and the need to improve and overcome legal conflicts in the regulatory acts of the specified area was established activity Discussion: on the basis of a comprehensive analysis of theoretical and legal foundations, normative foundations and practical implementation by state registrars of their powers in the field of state registration of property rights to immovable property and their encumbrances, the legislative foundations of the administrative and legal foundations of their activity were analyzed.